Dimethyl fumarate: a novel oral front-line therapy for multiple sclerosis treatment. (May 2013) - van Horssen, Jack; de Vries, Helga E
Owing to their immunomodulatory effects and safety profile, fumaric acid esters, such as dimethyl fumarate, are being investigated for the treatment of relapsing–remitting multiple sclerosis. BG-12, an oral formulation of dimethyl fumarate, is rapidly metabolized into its bioactive compound monomethyl fumarate, which displays both anti-inflammatory and neuroprotective properties in animal and in vitro studies. Although the mechanisms underlying the cytoprotective properties of fumaric acid esters are not fully elucidated, evidence is emerging that they act on immunomodulatory and antioxidant pathways. Clinical trials provide compelling evidence for the clinical efficacy of BG-12 in the treatment of relapsing–remitting multiple sclerosis, and have demonstrated that oral administration of BG-12 is well tolerated and markedly reduced the annualized relapse rate, the numbers of gadolinium-enhancing lesions and the number of black holes. Based on its favorable safety, tolerability and neuroprotective properties, BG-12 represents an excellent oral disease-modifying drug in the treatment of multiple sclerosis.